Strategic digital public relations in the Madiun Precinct Police: Insights from a public service perspective - Tanjung, Sumekar; Asmaí, Ahmad Fattah (Komunitas Ilmuwan dan Profesional Muslim Indonesia (KIPMI), 2024)
This research aims to explain the management of digital PR in the Madiun Precinct Police from the perspective of Phillips and Young. The achievements of the Madiun Precinct Police's PR are inseparable from the demands of digital technology and the capacity of the Madiun Precinct Police as a public service institution. The Madiun Precinct Police's PR utilizes digital PR not only to provide information but also to solidify public communication for the maintenance of public safety and order. With the role of PR and the achievements attained, this poses a challenge for the Madiun Precinct Police's PR in managing digital PR. A qualitative descriptive approach was employed by applying the five fundamental elements of digital PR by Phillips and Young, which include transparency, porosity, the internet as an agent, richness in content, and reach. The research findings indicate that the management of digital PR has been achieved with the readiness of an online system that includes supporting components such as platforms, channels, and context. Public information services are carried out clearly and openly, with information dissemination through the internet being controlled. The transformation of messages from PR to the public does not preclude the possibility of change. In the event of misinformation, PR will follow up incidentally. As public servants, the Madiun Precinct Police's PR is required to be capable of creating creative content and skilled in managing social media.